User Awareness on Electronic Resources and Services by Faculty and Students of NIFT Ranked Universities of Andhra Pradesh - Munugala Srinivasulu, Dasharadhi Ravinder (Mathematical Statistician and Engineering Applications, 2022)
The efficiency of electronic resources and services at certain university campuses of the Andhra Pradesh, which are NIRF ranked from 2016, is assessed based on user satisfaction. This study was conducted using a survey methodology. In the user survey, the researcher pickedseven university libraries inAndhra Pradesh. To collect information about the use of electronic resources and services, 180 well-structured questionnaires were administered. Students and faculty members received a total of 161 completed questionnaires, which were then analyzed, categorized , and tabulated using elementary statistical procedures. The research shows that most people who use the libraries are aware of the latest trends in electronic resources, services, and the appropriate use of these tools in the domains of education and research. The results showed that users are becoming more interested in e-resources and that slow downloading and blocking of websites make it harder for them to be used effectively. The poll also shows that most of the people who answered know how to use e-resources and services.